'Circuits of Victory': how the First World War shaped the political economy of the telephone in the United States and France. (3rd April 2019) - John, Richard R.; Laborie, Léonard
ABSTRACT: This essay contends that the US Signal Corps' wartime network had major consequences for the postwar development of the political economy of the telephone in the United States, France, and Europe. Our approach is transnational. In contrast to previous scholarship, which is mostly top-down, nation-centric, and preoccupied with the internal configuration of telephone networks that are typically studied inside the walls of discrete national containers, we widen the lens to explore a broad array of influences on network evolution, including those that originated from within individual operating companies and beyond national borders. Among the themes that we explore is transnational standard-setting. And among the agents of change that we emphasize is the influence of military conflict on personal networks, technical protocols, and international organizations. From such a vantage point, the First World War emerges as a constitutive moment in the making of the information infrastructure in the modern world.